THE COURSE OF DIABETIC POLYNEUROPATHY IN THE COMORBID DEFICITIES OF THE BODY (CLINICAL CASE) - Nodir K. Haydarov; Shakhlo B. Axrorova (Central Asian Journal of Medicine, 2023)
Today, the incidence of diabetes mellitus (DM) in the population is increasing at very high rates worldwide. Diabetic polyneuropathy (DPN) is the most common complication of diabetes mellitus (DM) in the peripheral nervous system. A common clinical form of DPN is a distal symmetrical, mainly sensory, polyneuropathy. The basis of the pathogenesis of DPN is chronic hyperglycemia, which leads to the accumulation of excess intermediate products in various organs and tissues, including damage to the vasa nervorum, which is involved in the blood supply of peripheral nerves. This article examines the deficiency states of the body in the case of diabetic and comorbid polyneuropathy.